THE INTERACTIONS OF REFUGEES, HUMAN RIGHTS, AND INTERNATIONAL LAW IN JORDAN (World Bulletin of Management and Law, 2022)
Refugees have become a major issue in the world within the past century. Syrian refugees are a major concern throughout the world, but specifically in Jordan. Jordan has taken in one of the highest numbers of Syrian refugees in the world. The researcher used the positional theory of adherence put forth by Kreps and Arend, which looks at the reason behind states following international law including the strength of the state in the international system, the normativity of the international law, the mechanisms to enforce the international law, and the extent to which the international law infringes on a state’s sovereignty, to determine the reasons Jordan would or would not follow the international refugee regime. The rights provided to refugees who did not go through the urban registration process were examined. The researcher hypothesized that Jordan would not provide adequate rights to refugees, but that there would be legal aid available to refugees to combat this. Several different theories of international relations, such as realism and constructivism, were examined to determine how well they applied in Jordan. Then Syrian refugees and professional working with Syrian refugees were interviewed to test the previous hypothesis.
Keywords: International; Regional Studies; Middle East